Perancangan Identitas Visual Warung Teras Kopi Untuk Membangun Brand Awareness - Joko Bintarto (Lembaga Pengembangan Kinerja Dosen, 2023)
At present the world of coffee in Indonesia is showing very rapid development. This is evidenced by the mushrooming of cafes or shops selling drinks from processed coffee throughout the archipelago. Coffee shop business owners are expected to increasingly compete for customers by serving quality coffee drinks, affordable prices and simpler outlet concepts. To maintain the existence of the mushrooming coffee shops, Teras Kopi needs a new, strong and consistent visual identity in order to be able to compete with other competitors who already have a strong and consistent visual identity. Based on these problems, the writer designed Warung Teras Kopi's visual identity using a descriptive approach, namely by directly interviewing related parties. As a result, this study uses the Graphic Standard Manual (GSM) which will be applied to supporting media properly and consistently, in accordance with the vision and mission of Warung Eras Kopi, so that it can become a new visual identity in the form of a new logo along with a newly created visual identity design. with the values ​​of coffee terrace coffee shops namely coffee, delicious, simple, and comfortable.